Effects of Disease Activity, Illness Perception, Social Support and Coping Methods on Quality of Life in the Patients with Rheumatoid Arthritis and Fibromyalgia Syndrome - Kesmen, Hakan; Cengiz, Ahmet Kivanc; Bilgici, Ayhan (BMJ Publishing Group, 2019)
…
Annual European Congress of Rheumatology (EULAR) -- JUN 12-15, 2019 -- Madrid, SPAIN